Women Empowerment in Comparison to Asian Female Gender Roles and Stereotypes in Crazy Rich Asians Novel - Hefandia, Deandra Alika; Kusuma, Dwi Linda; Ruslianti, Atikah (Journal of Languages and Language Teaching, 2023)
The issue regarding female gender roles has been circulating for so many years in many cultures. The issue can be seen in many media including a novel where it brings up the matter along the plot in the story. This article aims to see women empowerment in comparison to the female gender roles represented in Crazy Rich Asians novel by Kevin Kwan. To support this research, the theory used is Eagly’s Gender Role theory and Malhotra’s Women empowerment theory. The method used in this study is a descriptive qualitative method to elaborate on the female gender roles and women empowerment. The results showed that this novel portrays that the female gender roles and stereotypes came from the residual culture and the women empowerment happened when the female characters can choose their own life path for their own sake by their own decisions. It shows that despite the culture that bonds the female characters for generations, they can still speak up for themselves and choose what is good for them.